Aesthetic Technologies of Modernity, Subjectivity, and Nature : Opera, Orchestra, Phonograph, Film - Leppert, Richard D. (Book collections on Project MUSE., 2015)
"The book addresses how music (especially opera), the phonograph, and film served as cultural agents facilitating the many extraordinary social, artistic, and cultural shifts that characterized the nascent twentieth century and much of what followed long thereafter, even to the present. Three tropes are central: the tensions and traumas--cultural, social, and personal--associated with modernity; changes in human subjectivity and its engagement and representation in music and film; and the more general societal impact of modern media, sound recording (the development of the phonograph in particular), and the critical role played by early-century opera recording. A principal focus of the book is the conflicted relationship in Western modernity to nature, particularly as nature is perceived in opposition to culture and articulated through music, film, and sound as agents of fundamental, sometimes shocking transformation. The book considers the sound/vision world of modernity filtered through the lens of aesthetic modernism and rapid technological change, and the impact of both, experienced with the prescient sense that there could be no turning back"--Provided by publisher